THE EFFECT OF INDEPENDENT COMMISSIONERS, BOARD OF DIRECTORS SIZE, AND AUDIT OPINION ON THE TIMELINESS OF FINANCIAL REPORTING (A Study Of Manufacturing Companies In The Industrial Sector Listed On The Indonesian Stock Exchange For The 2020–2023 Period) - Mardiaton; Rifzan Fikra; Asy-Syura; Cut Putri Mellita Sari; Zulfan (CV. Radja Publika, 2026)
This study examines the role of Independent Commissioners, Board of Directors Size, and Audit Opinion in influencing the timeliness of financial reporting. Using a quantitative approach with panel data regression, secondary data from corporate financial statements were analyzed. Model selection through the Chow, Hausman, and Lagrange Multiplier tests indicated the Common Effect Model (CEM) as the most suitable. The findings show that, both individually and simultaneously, the three governance variables do not significantly affect reporting timeliness. The limited explanatory power of the model suggests that other factors outside governance mechanisms play a more dominant role. These results highlight the need for broader investigation into determinants of timely financial disclosure, particularly in emerging market contexts.